Assessing The Spillover Effects of The Indonesian Capital City (IKN) Development in North Penajam Paser Through Shift-Share Analysis - Wahyu Setyorini; Zidna Fitriyana (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2026)
Objective: The structural transformation of the economy in North Penajam Paser Regency has become massive as a result of the development of the Indonesian Capital City (IKN). This study analyzes the impact of sectoral spillovers and the potential for economic inequality arising from this development. Design/Methods/Approach: The quantitative Shift-Share Analysis method using the 2010 ADHK GRDP of Districts and Provinces, along with a descriptive review of the Gini Ratio indicator, was employed to analyze the period before and after the construction of IKN, specifically for the years 2021 and 2025. Findings: The research results show that the construction sector has the highest local competitive advantage score, confirming the absolute dominance of the capital city’s physical development as an economic driver. Positive values ​​for the trade, real estate, and accommodation sectors indicate a multiplier effect. However, the agriculture sector has the highest negative score due to land conversion and labor migration to infrastructure projects. The results also indicate the potential for structural and economic inequality. Originality/Value: The novelty of this research spans the massive construction phase through 2025 (the latest data), focusing not only on potential impacts. This research quantitatively demonstrates the existence of economic dualism in North Penajam Paser Regency, namely the highly uneven economic growth across sectors. Practical/Policy implications: The government needs to ensure that the spillover effects of the capital city’s development are inclusive. This requires strengthening the agricultural sector, developing local MSMEs, improving the quality of human resources, and ensuring equitable access.